Emotional Regulation, Peer Influence, Parenting Styles, Social Support, and Socio-Economic Status on Academic Performance among In-School Adolescents in Osogbo, Nigeria: A Structural Equation Modelling Approach - Akinyemi, Olukemi Yetunde (NIU Journal of Educational Research, 2025)
Academic performance is a critical determinant of student success and overall educational outcomes. Understanding the factors that influence academic achievement is essential for developing effective strategies to improve educational practices and support student success. This study investigated the influence of emotional regulation, peer influence, parenting styles, social support, and socio-economic status on academic performance among secondary school students in Osogbo, Osun State, Nigeria. Using a quantitative research design, the study involved 420 students from different academic streams (Science, Arts, and Commercial) in Senior Secondary 2 (SS2). A multi-stage sampling procedure was employed to ensure a diverse and representative sample. Data were collected through self-administered questionnaires, and academic performance data were obtained from school records. Structural Equation Modelling (SEM) was used to analyse the relationships between these factors and academic performance. The results indicated a significant predictive relationship between emotional regulation, peer influence, parenting styles, social support, socio-economic status, and academic performance. Specifically, emotional regulation had a moderate positive relationship with academic performance (β = 0.45, p = 0.001), while peer influence also showed a significant positive effect (β = 0.32, p = 0.002). Parenting styles and social support were both found to significantly influence academic performance, with estimates of β = 0.28 (p = 0.002) and β = 0.40 (p = 0.001), respectively. Additionally, socio-economic status (SES) was a significant predictor of academic success, with a positive relationship (β = 0.35, p = 0.000). Furthermore, the study found a significant interaction between these factors, which suggests that academic performance cannot be attributed to one factor alone but is instead shaped by the combined effects of emotional regulation, peer influence, parenting, social support, and socio-economic factors. The findings highlight the importance of considering the complex interplay of these variables in promoting academic success. This study provides important insights for educators, policymakers, and parents, particularly in socio-economically disadvantaged regions, and underscores the need for a holistic approach to addressing the factors that contribute to academic achievement in secondary education. Keywords: Emotional Regulation, Peer Influence, Parenting Styles, Social Support, Academic Performance